ANALISIS PENILAIAN DAN TANGGAPAN ALUMNI PERBANKAN SYARIAH PERIODE 2016-2018 - Melinda Lestari, Nur; Yeni, Fatma (Universitas Muhammadiyah Prof DR HAMKA, 2021)
The tracer study is a tracing study conducted for alumni of the Islamic Banking Department of the Islamic Faculty of UHAMKA who graduated in 2016, 2017, and 2018. Tracer Study is an important part of the existence of universities, especially the Sharia Banking study program in an effort to examine the links and matches of graduate quality in the world of work especially in Islamic banking financial institutions and non-banking Islamic financial institutions with learning services that have been provided during the study period in the Sharia Banking study program. The implementation of tracer studies in tertiary institutions is focused on tracking graduates in order to get feedback from the education/learning processes and services that have been carried out, both to alumni and users of graduates in society (stakeholders). Periodically, the UHAMKA Islamic Banking Study Program conducts a Tracer Study with the aim of improving the quality of learning services based on feedback from alumni and graduate users through this Tracer Study. The Tracer Study of the UHAMKA Islamic Banking Study Program was carried out for graduates in 2016, 2017, and 2018 starting from June to November 2020. The Tracer Study conducted at the UHAMKA Sharia Banking Study Program used the survey method for alumni who graduated two years ago and to the users. In-depth interviews were conducted with several alumni and selected graduate users to strengthen the findings of the tracer study for improving learning services in the UHAMKA Islamic Banking Study Program. The results show that the learning system implemented by the Sharia Banking Study Program can be said to be successful, it's just that the introduction of Al-Islam and Muhammadiyah has to be raised in the future. Data mining was carried out on an IT-based basis in order to reach all the targets of the Tracer Study targets. Keywords: Tracer Study, Islamic Banking, UHAMKA